Transformational Leadership in Efforts to Improve Teacher Performance - Emil Biyansyahna (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
This study aims to determine how transformational leadership can have an influence in efforts to improve teacher performance by the head or principal. This type of research is a qualitative descriptive study with interviews, observation and documentation of evidence in school institutions. The subjects in this research are principals, vice principals and teachers of SMP Muhammadiyah 3 Yogyakarta. The data analysis technique uses the data triangulation method, namely by narrating the strongest evidence of reality that appears at the research location. The triangulation method used includes: triangulation of data with sources and triangulation of data with methods. This study shows that transformational leadership has an influence on improving teacher performance so that teachers can perform performance that exceeds expectations. This study suggests that principals provide a habituation approach to maintain the stability of teacher performance.